Analysis of influence of certain elements of basketball game on final result based on differentiate at the XIII, XIV & XV World Championship - Simovic, S.; Komic, J. (Acta Kinesiologica, 2008)
In a basketball game, in which two teams play against one another, following the official FIBA rules and regulations, a team which scores more points wins a game. To identify a better team in a game is not always an easy task. Therefore, to predict the final result of a basketball game (especially the exact result) is very difficult, particularly in cases when the opponents are equally good or bad. In sports, as in life generally speaking, not always does a better team win. Of course, it depends on the influence of various factors, which lead to an expected result to take place or not. We can never be completely sure of the final result of a basketball game. Although some factors may indicate that a certain team stands better chances to win a game, shown by the observed parameters, still we cannot predict the result itself. Gathering, processing and analyzing of statistical data are the only worthy method based on which the causes of a successful or unsuccessful outcome of the game can be explained. On the basis of the found regularities we can account for the fact of whether or not, and to what extent, certain observed parameters may have had an influence on the final score thus influencing those parameters as to expect the result with a greater degree of certainty.